EARLY NEOPROTEROZOIC CRUST FORMATON IN THE DZABKHAN MICROCONTINENT, CENTRAL ASIAN OROGENIC BELT - V. P. Kovach; I. K. Kozakov; A. Kröner; E. B. Salnikova; K.-L. Wang; H.-Y. Lee; S.-L. Chung (Геодинамика и тектонофизика)
The Dzabkhan microcontinent was defined by [Mossakovsky et al., 1994] as a cratonic terrane with an early Precambrian basement that combines highgrade metamorphic complexes of the Songino, Dzabkhan, Otgon, Baidarik, Ider and Jargalant Blocks. However, early Precambrian ages have so far only been recognized in the Baidarik and Ider blocks [Kozakov et al., 2007, 2011; Kröner et al., 2015].